The Relationship Between Mental Toughness and Achievement Motivation of Sumedang Rugby Athletes - Cindy Sisilia; Dewi Susilawati; Aam Ali Rahman (Journal Coaching Education Sports, 2026)
Following a decline from winning the gold medal at the 2018 West Java Provincial Sports Week (PORPROV) to securing silver in 2022, the Sumedang Regency Rugby Association has faced challenges in maintaining athlete performance. Psychological factors, particularly mental toughness and achievement motivation, are considered essential determinants of athletic performance. This study aimed to examine the relationship between mental toughness and achievement motivation among Sumedang rugby athletes. A quantitative correlational design was employed involving 24 active rugby athletes selected through purposive sampling from a population of 28 athletes based on predetermined criteria, including active training participation and competition experience. Data were collected using validated Likert-scale questionnaires measuring mental toughness (14 items) and achievement motivation (34 items). Following confirmation of normality and linearity assumptions, data were analyzed using the Pearson Product-Moment correlation test at a significance level of 0.05. The analysis revealed a positive correlation between mental toughness and achievement motivation (r = 0.365); however, the relationship was not statistically significant (p = 0.356). These findings indicate that athletes with higher mental toughness tend to demonstrate greater achievement motivation, although the association was insufficient to reach statistical significance within the present sample. Future studies are recommended to involve larger samples and examine additional psychological and environmental factors influencing athletes' achievement motivation.